Properties of baked foams from oca (Oxalis tuberosa) starch reinforced with sugarcane bagasse and asparagus peel fiber - Cruz-Tirado, J.P. (2017)
ABSTRACT The aim of this work was evaluate the effect of the addition of sugarcane bagasse and asparagus peel fiber on the physical and mechanical properties of baked foams based on oca starch. Low concentrations of fiber reduce the density of the foams and the addition of fiber does not improve the flexural strength of the foams, but generates harder and deformable trays. High concentrations of sugarcane bagasse fiber generate more compact trays with a lower water absorption capacity than the control. Foams with asparagus peel fiber showed higher rates of thermal degradation than the control but not so extensive as to affect their applicability.